2019
DOI: 10.1002/ange.201900613
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of Fused Tri‐ and Tetrasubstituted Aziridines: aza‐Darzens Reaction of Cyclic Imines with α‐Halogenated Ketones Catalyzed by Bifunctional Phosphonium Salt

Abstract: The first enantioselective aza-Darzens reaction of cyclic imines with a-halogenated ketones was realized under mild reaction conditions by using amino-acid-derived bifunctional phosphonium salts as phase-transfer promoters.A variety of structurally dense tri-and tetrasubstituted aziridine derivatives,c ontaining benzofused heterocycles as well as spiro-structures,w ere readily synthesized in high yields with excellent diastereo-and enantioselectivities (up to > 20:1 d.r. and > 99.9 %ee). The highly functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Recently, Wang and co‐workers successfully realized a highly efficient aza‐Darzens reactions between cyclic keto‐imines 54 and α‐halogenated ketones 55 by using dipeptide‐based phosphonium salt U , and a range of trisubstituted aziridines 56 were generated via this method (Scheme ) . Control experiments for explaining the role of hydrogen bond were also performed, no high ee values could be obtained when the amide N—H were protected by methyl group.…”
Section: Bifunctional Phosphonium Salts Derived From Chiral Amino Acidsmentioning
confidence: 99%
“…Recently, Wang and co‐workers successfully realized a highly efficient aza‐Darzens reactions between cyclic keto‐imines 54 and α‐halogenated ketones 55 by using dipeptide‐based phosphonium salt U , and a range of trisubstituted aziridines 56 were generated via this method (Scheme ) . Control experiments for explaining the role of hydrogen bond were also performed, no high ee values could be obtained when the amide N—H were protected by methyl group.…”
Section: Bifunctional Phosphonium Salts Derived From Chiral Amino Acidsmentioning
confidence: 99%
“…They are also versatile building blocks for the assembly of a variety of diversely functionalized benzosultam derivatives and other heterocyclic systems. In this context, various transformations have been developed, such as dipolar cycloaddition [ 14 , 15 ], nucleophilic addition [ 16 , 17 , 18 , 19 , 20 , 21 ], transition metal-catalyzed C–H activation/annulation [ 22 , 23 , 24 , 25 ], Corey–Bakshi–Shibata reduction, and Aza-Darzens condensation [ 26 , 27 ] etc., which extensively expand their application range in the area of synthetic chemistry. Therefore, the development of convenient methods for the efficient preparation of benzosultams play important roles in drug discovery and asymmetric synthesis, which have attracted much attention from synthetic chemists.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The Dieckmann reaction was firstly investigated using easily synthesized 3-substituted N-benzyl oxindoles 1 a, and the phosphonium salts (3 a-3 e) bearing distinct amino acid backbones were initially used to investigate the performance of enantioselective control on the reactions. [11] It demonstrated that the reactions occurred very effectively under the catalysis of phosphonium salts and K 2 CO 3 as the base. Fortunately, 3 e produced from isoleucine proved to be the most effective, furnishing the cyclic product 2 a in high yield, but with only 64% ee (Table 1, entries 1-5).…”
mentioning
confidence: 98%